The Measurement Analysis of Online Service Quality Toward State Banking Customers Using Structural Equation Modeling - Sudirjo, Frans; Candra Dewi, Luh Komang; Desty Febrian, Wenny; Sani, Indra; Dharmawan, Donny (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to evaluate the level of customer care offered online so that users can keep using the e-banking system as they see fit. In order to gather data for e-banking system study, involved parties' questionnaire responses, interviews, and observations are used. Furthermore, it is necessary to perform a literature evaluation pertaining to this topic. Researchers both directly and indirectly distributed questionnaires as part of the data collection process. In the first stage, non-probability sampling is performed, and in the subsequent stage, purposive sampling is used based on predetermined criteria. 100 people made up the sample in this study. The Structural Equation Modeling (SEM) method was the data analysis technique used in this study. The study's findings demonstrated that users of the e-banking system were more likely to trust the caliber of the services offered. Customers can feel satisfied and assured when using the e-banking system because it provides what they need. Because the e-banking system's quality service has a relatively high value in relation to the probability value of its variable values, clients can feel confidence when transacting with it. The e-banking system is able to make clients feel content, hence it has a major influence on customer loyalty, even though the value is fairly tiny compared to the likelihood values for other variables.